Identification of Rare Medical Plant and Community Understanding in Manggeh Village, Karanganyar District, Karanganyar Regency - Farhah Qurrotu 'Aini; Nur Rokhimah Hanik; Tri Wiharti (Jurnal Biologi Tropis, 2023)
This study aims to identify rare medicinal plants in Manggeh Village, Karanganyar District, Karanganyar Regency, as well as to understand the level of knowledge and understanding of the community regarding rare medicinal plants in areas with a low tendency. The research method used was field surveys, interviews, and direct observation of 40 respondents who were randomly selected from people in low inclined areas. The results showed that there were a number of rare medicinal plants in Manggeh Village. These plants have high medicinal potential and have been used traditionally by the local community. However, the level of public knowledge and understanding regarding rare medicinal plants is still limited. Although some people are familiar with rare medicinal plants in general, in-depth knowledge about their benefits, uses and potential side effects is still limited. This research provides a deeper understanding of the biodiversity in Manggeh Village and provides useful information for the community in the proper and responsible use of medicinal plants. The results of this study can also be a basis for local governments in developing policies for the conservation of rare medicinal plants.